Use of Carboxyhemoglobin as an Early Sign of Oxygenator Dysfunction in Patients Supported by Extracorporeal Membrane Oxygenation - Cousin, Vladimir L.; Giraud, Raphaël; Assouline, Benjamin; Silva, Ivo Neto; Bendjelid, Karim (Frontiers in Medicine, 2022)
Introduction: Plasma free haemoglobin is the gold standard for monitoring haemolysis in extracorporeal membrane oxygenation (ECMO) but its routine use has some limitations. Carboxyhaemoglobin is also a marker of intravascular haemolysis. We aimed to investigate carboxyhaemoglobin as a marker of both haemolysis and oxygenator dysfunction in patients supported by extracorporeal membrane oxygenation (ECMO). Methods: Retrospective analysis of patients on ECMO in an adult ICU in a tertiary hospital. HbCO was recorded every 6 hours in the 48 hours before and after oxygenator change in adult patients on ECMO support with an oxygenator dysfunction and replacement. Results: The investigation of 27 oxygenators replacements in 19 patients demonstrated that HbCO values progressively increased over time and then significantly decreased after oxygenator change. Median oxygenator lifespan was 14 days (IQR 8-21) and there was no correlation between HbCO and oxygenator lifespan (Spearman coefficient 0,23 (p = 0,23)). HbCO values at oxygenator change (HbCO median 2,7 (IQR 2,5-3,5)) were significantly higher than the HbCO values one week before (HbCO median 2,07 (IQR 1,86-2,8)) (p value <0,001). Conclusion: Our data highlight the potential role of HbCO as a novel marker for ECMO oxygenator dysfunction.